Joint Optimal Scheduling of Renewable Energy Regional Power Grid With Energy Storage System and Concentrated Solar Power Plant - Dong, Yannan; Han, Zijiao; Li, Xiangjun; Ma, Shaohua; Gao, Fulin; Li, Wenwen (Frontiers in Energy Research, 2022)
Under the path of global low-carbon development, increasing the proportion of renewable energy in power grid will become the main goal in the future. But it will also aggravate the problem of wind and solar curtailment. A joint optimal scheduling model of renewable energy regional power grid with energy storage system and concentrated solar power plant is proposed in this paper. The proposed model taking the lowest comprehensive operation cost of power grid as the optimization goal, and considers various constraints of concentrated solar power plants, energy storage systems, thermal power units, wind power and photovoltaic power generation. Finally, a modified IEEE 9-bus system is used to to verify the validity. The results show that the model can effectively improve the system node voltage, promote the accommodation of wind and solar, and alleviate the peak shaving of thermal power units under the premise of the optimal economy pressure.